To study the level of congestion in Pre anesthetic Check up (PAC) clinic and use of Self-answering Pre-operative questionnaire to decongest it - Kumar Singh, Manish; Bhatia, Kiran; Tobin, Raj; Waindeskar, Vaishal; Kumar, Amit; Sharma, Punit (International Journal of Medical Research and Review, 2019)
Background: Aim of the study was to reduce congestion in PAC clinic, which is the direct indicator of efficiency of the hospital. 1) To study overall waiting time in the PAC clinic. 2) To suggest action to improve the waiting time in PAC. Methods: Prospective, Descriptive study, 40 patients in each group. Group “R” = Patients registered for PAC clinic, who’s all vitals and clinical assessment was done after arrival to PAC clinic as routine practice. Group “Q” = Patients were provided Self-answering Pre-operative in waiting area and whose vital parameters were taken before arrival to PAC clinic by a trained staff. Data was recorded for both the groups. Results: We found in our study that average waiting time that is total time from registration to completion of PAC in OPD clinic was statistically significantly less in QT-1 (Group “Q”) in comparison to RT-1 (Group “R”). We found in our study that average Doctor – Patient time that is time of interaction with Doctor during PAC in OPD clinic was also statistically significantly less in QT-2 (Group “Q”) in comparison to RT-2 (Group “R”). Conclusion: Present study was planned to reduce congestion in OPD for pre-anesthesia checkup for elective surgery or procedure. Patient satisfaction comes automatically as a byproduct with the achievement of the goal of the study. Time is money in the present scenario and thus best utilization of time with efficient outcome is the prerequisite of any good management.